Relationship between microbiology of throat swab and clinical course among primary care patients with acute cough: a prospective cohort study. (17th December 2019) - Ordóñez-Mena, José M; Fanshawe, Thomas R; Butler, Chris C; Mant, David; Longhurst, Denise; Muir, Peter; Vipond, Barry; Little, Paul; Moore, Michael; Stuart, Beth; Hay, Alastair D; Thornton, Hannah V; et al.
Abstract: Background: Acute lower respiratory tract infections (ALRTIs) account for most antibiotics prescribed in primary care despite lack of efficacy, partly due to clinician uncertainty about aetiology and patient concerns about illness course. Nucleic acid amplification tests could assist antibiotic targeting. Methods: In this prospective cohort study, 645 patients presenting to primary care with acute cough and suspected ALRTI, provided throat swabs at baseline. These were tested for respiratory pathogens by real-time polymerase chain reaction and classified as having a respiratory virus, bacteria, both or neither. Three hundred fifty-four participants scored the symptoms severity daily for 1 week in a diary (0 = absent to 4 = severe problem). Results: Organisms were identified in 346/645 (53.6%) participants. There were differences in the prevalence of seven symptoms between the organism groups at baseline. Those with a virus alone, and those with both virus and bacteria, had higher average severity scores of all symptoms combined during the week of follow-up than those in whom no organisms were detected [adjusted mean differences 0.204 (95% confidence interval 0.010 to 0.398) and 0.348 (0.098 to 0.598), respectively]. There were no differences in the duration of symptoms rated as moderate or severe between organism groups. Conclusions: Differences in presenting symptoms and symptoms severity can be identified between patients with viruses and bacteria identified on throat swabs. The magnitude of these differences is unlikely to influence management. Most patients had mild symptoms at 7 days regardless of aetiology, which could inform patients about likely symptom duration.